The Analysis of Sense Relations Found in Trending Topics of NIKKEI ASIA Newspaper : The Analysis of Sense Relations Found in Trending Topics of NIKKEI ASIA Newspaper - Pina, Pina Barokah (LP3MKIL, 2024)
The research aimed to describe the kinds of sense relations and to determine the meaning of sense relations used in the trending topics of NIKKEI ASIA newspaper. The method of the research was descriptive qualitative. The data sources obtained from the NIKKEI ASIA newspaper that published for a week that contained from June, 09 – 15th 2024. There were 7 article titles such as; Africa’s Copperbelt sets off race for EV metals, U.N. Chief says Russia must uphold North Korea sanctions, Malaysia and Thailand keen to Join BRICS: 5 things to know, China Presses Global Leaders to Support Taiwan ‘reunification’, Biden-Trump debate: Where they stand on China and Taiwan, India’s Congress party vows to fight ‘fascist rule’ of Modi’s BJP, and Japan’s Chip Industry can be revived, Acer cofounder says as the subject of the research. The technique of collecting the data was documentation. In the procedures for analyzing data, the researcher used six steps: the first step was preparing and organizing the data, the second step was to explore and codes. The next step or third was coding the data. The fourth step was describing the data. The fifth step was representing the data. Finally, the last step was interpreting the data. The results showed there were 12 data of synonymy, 3 data of hyponymy, 5 data of antonymy, and 3 data of ambiguity. Therefore, the researcher found all kinds of sense relations and determined the meaning of them with 23 data in total based on the general meaning (oxford dictionary) and contextual meaning of the sentences. In conclusion, the trending topics of NIKKEI ASIA newspaper contained all aspects of sense relations.